Induced Piezoelectricity in Cotton-Based Composites for Energy-Harvesting Applications - Tiwari S.; Devi A.; Dubey D.K.; Maiti P. (My University, 2025)
A flexible and easily processable polymer composite is developed from naturally occurring piezoelectric materials for efficient energy-harvesting applications. Tomato peel (TP)- and cotton (CTN)-based poly(vinylidene fluoride) (PVDF) composites have been prepared and the role of induced electroactive phases have been explored through structural, thermal, and morphological analyses for their applications in energy production. The mechanism of induced piezoelectricity is vividly demonstrated using electromechanical responses and characteristic changes due to induction phenomena. The CTN-based composite generates a maximum output voltage and current of 65 V and 2.1 μA, respectively, as compared to the maximum output voltage and current of 23 V and 0.7 μA in TP-based composites due to the significant induction of the piezoelectric phase in the presence of suitable electroactive cotton. The fabricated device is able to store charges in capacitors and converts the external stress through different motions of the human body to generate a considerable output, which describes the applicability of the material and justifies the potential as an efficient and sustainable biomechanical energy harvester. © 2023 American Chemical Society.